Empirical Analysis of the Assessment of Innovation Effects in U.S. Merger Cases - Benjamin R. Kern; Ralf Dewenter; Wolfgang Kerber (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
In this empirical study all mergers that have been challenged by the U.S. antitrust agencies FTC and DOJ between 1995 and 2008 were analyzed in regard to the question to what extent and how the agencies assessed the innovation effects of mergers. Theoretical background is the still open question how negative effects of mergers on innovation should be taken into account in merger policy. Although we can show in our study that in one third of all challenged mergers also innovation concerns were raised, the results also point to a still existing large degree of uneasiness and inconsistencies of the agencies in regard to the assessment of innovation effects. A particularly interesting result is that - despite the wide-spread rejection of the "innovation market approach" in the antitrust debate - the agencies used more an innovationspecific assessment approach that includes also innovation in the market definition than the pure traditional product market concept. Additionally, we also found significant differences between the assessment approaches of the FTC and the DOJ.
Keywords: K21; L12; L41; O31; 330; innovation; merger policy; US antitrust; innovation market